Correlation between Self-Efficacy and Motivation with Self-Direct Learning of Elementary School Students: Korelasi antara Efikasi Diri dan Motivasi dengan Kemandirian Belajar Siswa Sekolah Dasar - Alfiyah, Hanifah Dian; Habiby, Wahdan Najib (Pedagogia : Jurnal Pendidikan, 2025)
Students’ low self-directed learning is often attributed to insufficient external support, leading to poor academic habits and dependency on rewards. Such conditions may reduce knowledge retention and weaken both self-efficacy and learning motivation. Despite its importance, the interplay between internal factors like self-efficacy and learning motivation in fostering self-directed learning among elementary students remains underexplored. This study investigates the relationship between self-efficacy and motivation to learn through self-directed learning in upper-grade elementary students in Surakarta. Using a quantitative correlational approach, data were collected from 140 students through Proportional Random Sampling and analyzed using product moment and multiple correlation techniques. The findings show a significant positive correlation between self-efficacy and self-directed learning (r = 0.556, p < 0.05), and between learning motivation and self-directed learning (r = 0.630, p < 0.05). Both variables together also significantly correlate with self-directed learning (R = 0.649, p < 0.05). This study empirically confirms the dual role of self-efficacy and motivation as predictors of self-directed learning among elementary students. The results highlight the importance of fostering internal factors to enhance learning independence, while encouraging further research into additional influences such as external support, time management, and learning strategies. Highlights: Self-efficacy and learning motivation have a significant positive correlation with students' independent learning. Correlation analysis shows that self-efficacy and learning motivation jointly contribute to increased learning independence (R = 0.649; p < 0.05). Independent learning is influenced by internal factors, particularly students’ confidence and intrinsic motivation. Keywords: Self-Efficacy, Learning Motivation, Self-Direct Learning